Evaluation of flavor and nutritional properties of quinoa seeds in the diet of broiler chickens - Sergeenkova N.A.; Vertiprakhov V.G.; Karamushkina S.V.; Grigoriev A.M. (Ветеринария и кормление)
Experiments were performed on 15-45-day-old broiler chickens of the cross "Change 9" with duodenal fistula. Chyme was collected in the morning on an empty stomach daily twice in 60 and 120 minutes after feeding, in the supernatant the activity of trypsin, alkaline phosphatase, calcium and phosphorus content were investigated. The nutritional content of the control feed corresponded to the recommended norms for this cross of broiler chickens and contained an additive of white lupin of Timiryazevskaya selection, replacing soybean meal in the amount of 15.0%. Experimental diets contained the addition of quinoa seeds of two varieties. The results of the studies showed that the addition of quinoa seeds to the feed (1.0% of feed weight) caused an increase in trypsin activity 60 minutes after feeding by 83.9%, 120 minutes after feed intake - by 102.0% compared to the indicators of 1 control group. This indicates a positive palatability response of poultry to quinoa seed supplementation. Protein hydrolysis in the intestine increased markedly with increased trypsin activity. Total phosphorus content in the intestine increased with the presence of saponins in quinoa, similar trend was observed in alkaline phosphatase activity. When quinoa seeds were added to the diet of broiler chickens, blood trypsin activity decreased by 34.7% (p<0.05), indicating a slowdown in metabolism. At the same time, feed intake of poultry decreased due to rapid saturation with high-protein feed. Amylase activity decreased in the experimental group by 21,9% (p<0,05), triglyceride content in the blood of experimental chickens decreased by 40.8% (p<0.05). There was a decrease in blood total phosphorus by 41.6% (p<0.05), which was due to lower hydrolysis of phosphorus compounds by alkaline phosphatase. In general, when intestinal digestion was improved by quinoa supplementation at a dose of 1.0% of feed weight, there was a slowdown in carbohydrate and lipid metabolism, which may be due to an impaired protein ratio in the diet.